Research on CMOS Devices Based on Wide Bandgap Semiconductor Materials - Ding , Yuehang (Transactions on Computer Science and Intelligent Systems Research, 2024)
Considerable financial resources have been allocated towards the design and development of wide and ultra-wide bandgap semiconductor circuits due to their use in power and radio frequency electronics. This is due to the fact that these circuits possess the capability to accomplish these tasks. Due to their minimal loss rates and capacity to rapidly switch high currents and voltages, these devices exhibit great versatility. The presence of parasitic effects in silicon-based CMOS circuits, which are necessary for the integration of intricate control logic, often hinder the performance of end systems that use these devices. This is a difficulty since these circuits are crucial for the execution of intricate control logic. A viable technique that has recently evolved involves directly incorporating CMOS circuitry into a wide bandgap substrate, which is suitable for a range of mature materials. This approach has developed a functional technology. The objective of this study is to examine the present condition of CMOS technology in wide bandgap materials such as diamond, SiC, and GaN, with the aim of analysing its current situation. The findings of this study article provide useful insights that might be used in the advancement of energy-efficient electronic gadgets with enhanced performance capabilities.